Peran Kepemimpinan Efektif dan Pendidikan Latihan Terhadap Kemampuan Intelejen Prajurit Batalyon 21 Grup 2 Kopassus - Pratama, Septuci; Madiistriyatno, Harries; Kusumadewi, Nurwulan (Excellent, 2025)
The purpose of this study is as follows To determine the Influence of Effective Leadership and Training Education on the Intelligence Ability of Soldiers. The number of samples studied was 100 respondents of Soldiers of Battalion 21 Group 2 Kopassus. The software used to support this research is the SPSS (Statistical Product and Service Solutions) Version 29 program. the conclusion of the test with this method is the coefficient value of the Effective Leadership variable, namely 0.315 and the significance value is 0.001. The coefficient value of the Education and Training variable is 0.275 and the significance value is 0.000. This means that the variables studied have a positive and significant impact on Soldier Intelligence Ability.